Dislocation of the gastric conduit reconstructed via the posterior mediastinal route is a significant risk factor for anastomotic disorder after McKeown esophagectomy. Issue 1 (12th August 2021) - Nakajima, Masanobu; Muroi, Hiroto; Kikuchi, Maiko; Fujita, Junki; Ihara, Keisuke; Nakagawa, Masatoshi; Morita, Shinji; Nakamura, Takatoshi; Yamaguchi, Satoru; Kojima, Kazuyuki
Abstract: Background: Anastomotic disorder of the reconstructed gastric conduit is a life‐threating morbidity after thoracic esophagectomy. Although there are various reasons for anastomotic disorder, the present study focused on dislocation of the gastric conduit (DGC). Methods: The study cohort comprised 149 patients who underwent transthoracic esophagectomy. The relationships between DGC and peri‐ and postoperative morbidities were analyzed retrospectively. Data were analyzed to determine whether body mass index (BMI) and extension of the gastric conduit were related to DGC. Uni‐ and multivariate Cox regression analyses were performed to identify the factors associated with anastomotic disorder. Results: DGC was significantly related to anastomotic leakage ( P  < .001), anastomotic stricture ( P  = .018), and mediastinal abscess/empyema ( P  = .031). Compared with the DGC‐negative group, the DGC‐positive group had a significantly larger mean preoperative BMI (23.01 ± 3.26 kg/m 2 vs. 21.22 ± 3.13 kg/m 2, P  = .001) and mean maximum cross‐sectional area of the gastric conduit (1024.75 ± 550.43 mm 2 vs. 619.46 ± 263.70 mm 2, P  < .001). Multivariate analysis revealed that DGC was an independent risk factor for anastomotic leakage (odds ratio: 4.840, 95% confidence interval: 1.770‐13.30, P  < .001). Body weight recovery tended to be better in the DGC‐negative group than in the DGC‐positive group, although this intergroup difference was not significant. Conclusion: DGC reconstructed via the posterior mediastinal route is a significant cause of critical morbidities related to anastomosis. In particular, care is required when performing gastric conduit reconstruction via the posterior mediastinal route in patients with a high BMI. Abstract : Anastomotic disorder is a life‐threating morbidity after esophagectomy. Anastomotic leakage, stricture, and mediastinal abscess/empyema are significantly related to dislocation of the gastric conduit.